Tanggungjawab Pemerintah Dan Pelaku Usaha Makanan Siap Saji Terkait Penggunaan Wadah Plastik Yang Berbahaya Bagi Konsumen Di Kota Ambon - Agustina Balik; Vica Jilyan Edsti Saija (Faculty of Law, Universitas Pattimura, 2017)
Plastic containers are the most popular food packaging materials used. Many businesses choose plastic as a container for their products, because the plastic has excellent properties such as: strong but light, practical, cheap and not out of date. Though it use is very dangerous because can happen migration of chemicals from plastic to food wrapped especially in the heat. The role of BPOM (Food and Drug Supervisory Agency) and the Office of Industry and Trade on Consumer Protection has not been effective in socializing the dangers of using plastic as a food packaging container. The research method used is the normative juridical research method to examine the legal material, the provisions of positive law, legal principles, legal principles and legal doctrine to answer the legal issues faced. The form of supervision is part of the function and at the same time is the responsibility of BPOM and the Office of Industry and Trade in the field of Consumer Protection in an effort to provide protection to the community. demanded knowledge and awareness of business actors in choosing containers used to wrap food to be purchased by consumers. Responsibility on the basis of an error may be imposed on a business actor if the business actor makes a mistake that harms another person. While the absolute responsibility of direct business actor is responsible as business risk. Therefore, for a business actor who uses a plastic container that is harmful to human safety, he or she may be held liable for damages